The Effect of Location and Quality of Services on the Decision of Saving Customers at BNI KCP Bintuhan, Kaur Regency - Olan Rizki; Nia Indriasari; Iswidana Utama Putra (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine the influence of emotional intelligence and work achievement on the performance of State Civil Apparatus at the Regional Secretariat of Kaur Regency. The sample in this study was 79 State Civil Apparatus (ASN) at the Regional Secretariat of Kaur Regency. The data was collected using a questionnaire and the analytical methods used were multiple linear regression, determination test and hypothesis testing. The results of the regression analysis showed Y = 8,641 +0,312X1 +0,492 X2, this describes a positive regression direction, meaning that there is a positive influence between X1 (emotional intelligence) and X2 (work achievement) on performance (Y). It means that if the variables of emotional intelligence and work achievement increase, it will increase performance. The value of the coefficient of determination is 0.501. This means that X1 (emotional intelligence) and X2 (work achievement) affect performance (Y) by 50.1% while the remaining 49.9% is influenced by other variables not examined in this study. The significance of 0.05 explains that partially emotional intelligence and work achievement variables have a significant influence on the variable performance of State Civil Apparatus at Regional Secretariat of Kaur Regency. The results of F test at a significance level of 0.05 explained that the variables of emotional intelligence and work achievement had a significant influence on performance of State Civil Apparatus at the Regional Secretariat of Kaur Regency.